The democratic management of the public school in contexts of local educational reforms: A comparative study between Brazil and Spain - Neusa Chaves Batista; Miguel A. Pereyra (Arizona State University, 2020)
Democratic management as a way of organizing the public school can be translated in its contemporary historicity as a collective action that demands changes in the autocratic and hierarchical structure of the school unit. In this article, we analyze the process of constructing legislation on democratic school management in contexts of local educational reforms, based on Brazilian and Spanish cases. Methodologically, we understand educational legislation as documents that incorporate discourses with legitimate authority, especially of the State, and that spread conceptions of the world as a result of disputes over hegemony in the field of educational policies. In terms of results, our study points out that throughout the process of producing legislation for the democratic management of schools, the two countries showed advances and setbacks regarding the specification of the school actors who should participate in decision-making processes, as well as the instances of participation in school management.